Table of Content - - (Journal of natural sciences, life and applied sciences, 2025)
:Table of Content• Utilization of the Byproduct from Phonolite Rock Exploitation in the Production of Ceramic BodiesDr. Halima Al-Shaibani Abusriwil, Ms. Numidia Fouad Ftis• Monitoring Sand Encroachment on Highways in the Qassim Region Using Remote Sensing  and Geographic Information SystemsMs. Fidaa Sulaiman Al-Omar, Prof. Mohammed Ibrahim Al-Dughairi• Evolution of the Lower Valley of Oued Za during the Quaternary (Northeastern Morocco)Dr. BENHAMED Abderrahim, PES. SBAI Abdelkader• Effectiveness of Urban Parks in Reducing Surface Temperatures in Riyadh City Using Remote Sensing and Geographic Information SystemsDr. Haya Falah Al-Shahrani
Keywords: Journal of Natural Sciences, Life and Applied Sciences